Two-photon absorption and excitation spectroscopy of carotenoids, chlorophylls and pigment–protein complexes. Issue 14 (30th March 2021) - Gacek, Daniel A.; Betke, Alexander; Nowak, Julia; Lokstein, Heiko; Walla, Peter J.
Abstract : Comparing carotenoid and chlorophyll two-photon spectra with that of light harvesting complexes shows the latter consist of both. Depending on the two-photon excitation (TPE) wavelength, mainly carotenoid dark states or chlorophylls can be excited. Abstract : In addition to (bacterio)chlorophylls, (B)Chls, photosynthetic pigment–protein complexes bind carotenoids (Cars) that fulfil various important functions which are not fully understood, yet. However, certain excited states of Cars are optically one-photon forbidden ("dark") and can potentially undergo excitation energy transfer (EET) to (B)Chls following two-photon absorption (TPA). The amount of EET is reflected by the differences in TPA and two-photon excitation (TPE) spectra of a complex (multi-pigment) system. Since it is technically and analytically demanding to resolve optically forbidden states, different studies reported varying contributions of Cars and Chls to TPE/TPA spectra. In a study using well-defined 1 : 1 Car–tetrapyrrole dyads TPE contributions of tetrapyrrole molecules, including Chls, and Cars were measured. In these experiments, TPE of Cars dominated over Chl a TPE in a broad wavelength range. Another study suggested only minor contributions of Cars to TPE spectra of pigment–protein complexes such as the plant main light-harvesting complex (LHCII), in particular for wavelengths longer than ∼600/1200 nm. By joining forces and a combined analysis of all available data by both teams, we try to resolve this apparent contradiction. Here, we demonstrate that reconstruction of a wide spectral range of TPE for LHCII and photosystem I (PSI) requires both, significant Car and Chl contributions. Direct comparison of TPE spectra obtained in both studies demonstrates a good agreement of the primary data. We conclude that in TPE spectra of LHCII and PSI, the contribution of Chls is dominating above 600/1200 nm, whereas the contributions of forbidden Car states increase particularly at wavelengths shorter than 600/1200 nm. Estimates of Car contributions to TPA as well as TPE spectra are given for various wavelengths.